Acceleration of hybrid MPI parallel NBODY6++ for large N-body globular cluster simulations. Issue Volume 10:Issue S312(2014) (7th March 2016) - Wang, Long; Spurzem, Rainer; Aarseth, Sverre; Nitadori, Keigo; Berczik, Peter; Kouwenhoven, M.B.N.; Naab, Thorsten
Abstract: Previous research on globular clusters (GCs) dynamics is mostly based on semi-analytic, Fokker-Planck, Monte-Carlo methods and on direct N -body (NB) simulations. These works have great advantages but also limits since GCs are massive and compact and close encounters and binaries play very important roles in their dynamics. The former three methods make approximations and assumptions, while expensive computing time and number of stars limit the latter method. The current largest direct NB simulation has 500k stars (Heggie2014 ). Here, we accelerate the direct NB code NBODY6++ (which extends NBODY6 to supercomputers by using MPI) with new parallel computing technologies (GPU, OpenMP + SSE/AVX). Our aim is to handle large N (up to 10 6 ) direct NB simulations to obtain better understanding of the dynamical evolution of GCs.